In quest of a shared planet : negotiating climate from the Global South - Khan, Naveeda Ahmed, 1969- (New York : Fordham University Press, 2023)
"...In Quest of a Shared Planet is a stirring call to action that highlights the key role responsive and active youth have in climate negotiations. It is an invitation not only to understand the climate negotiation process but also to navigate and critique it, with sympathy and an eye to viable alternatives."--Back cover
List of acronyms and abbreviations -- Bodies under the UNFCCC -- Introduction: the climate regime -- How to COP -- The voice of Bangladesh -- Who wants to be a negotiator -- Politics in between-spaces -- Accounting for change in the Paris Agreement -- A thrice-told tale of negotiations -- The house of loss and damage -- Conclusion: the gift of the Global South --Acknowledgments -- Notes -- Bibliography -- Index
Included bibliographical references (pages 195-218) and index.
ENH
Book Finder International
Keywords: Climatic changes -- Developing countries; Climatic changes -- International cooperation; Climatic changes; Climatic changes -- International cooperation; Developing countries